(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Analysis of the swelling process revealed some differences in the kinetics in A. pskemense B. Fedtsch. from 2 other representatives of the genus Allium L. – A. aflatunense B.Fedtsch. and A. altissimum Regel. A. pskemense B. Fedtsch plants were introduced into in vitro culture on Murashige and Skoog + 0.5 6-benzylaminopurine medium. Callus culture obtained from the roots on Murashige and Skoog medium with the addition of 1.0 mg/l of 2,4-dichlorophenoxyacetic acid, 0.2 mg/l of 6-benzylaminopurine and 30 g/l of sucrose. The period of callus formation is about 3 months.